Does rubber expansion hinder the migration of rural labor? Evidence from southwest China?. Issue 2 (4th February 2022) - Yang, Ningan; Ding, Yawen; Min, Shi; Bai, Junfei
Abstract: The expansion of agroforestry crops in South Asia has resulted in the reallocation of local agricultural resources, including labor force. Based on two‐wave panel data collected from more than 600 smallholder rubber farmers in southwest China, this study examines the impacts of rubber expansion on the migration of rural labor. The results show that smallholders planting more rubber plantations have significantly fewer migrant family members and lower likelihood of migration, revealing a significantly negative effect of rubber cultivation on the migration of rural labor. Given that the migration of rural labor is a major trend in rural economic transformation, rubber farming appears to result in the resource curse in rubber planting areas. In addition, a positive interaction effect between rubber cultivation and the price of natural rubber on the migration of rural labor reveals that the resource curse effect of natural rubber decreases with the decrease in the price of natural rubber. A period with a relatively low price of natural rubber provides an opportunity to foster the migration of rural labor in rubber planting areas.